The allocation of regulatory competence in the EU emissions trading scheme / Josephine van Zeben. - Zeben, Josephine A. W. van, 1984- (Cambridge studies in European law and policy., 2014)
The European Union's Emissions Trading System (EU ETS) is the world's largest carbon trading market. This book offers a new perspective on the EU ETS as a multi-level governance regime, in which the regulatory process is composed of three distinct 'competences' - norm setting, implementation, and enforcement. Are these competences best combined in a single regulator at one level of government or would they be better allocated among a variety of regulators at different levels of government? The combined legal, economic, and political analysis in this book reveals that the actual allocation of competences within the EU ETS diverges from a hypothetical ideal allocation in important ways, and provides a political economy explanation for the existing allocation of norm setting, implementation and enforcement competences among various levels of European government.